Synthesize and characterization of clay based low-cost membrane for solid-liquid separation - Anandkumar, J; Sahariah, Biju Prava; Dasgupta, Soumendu (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> In this work, locally available clay material was mixed with inorganic materials to synthesize the low-cost ceramic membrane in microfiltration range. Membrane was sintered at different temperatures (800-950oC) and the effect of sintered temperature on membrane preparation was studied in detail. The membrane porosity was found to decrease (44-30%) with membrane sintering temperatures (800-950oC). The corrosion resistance of the prepared ceramic membranes at different sintering temperatures was analyzed using N-methyl-2-pyrrolidone (NMP), NaOH and HCl. It was observed that the elemental composition by EDX analysis and porosity measurement of the synthesized membrane was found almost invariant. Finally, the synthesized membranes were characterized by scanning electron microscope (SEM) and Fourier transform infrared (FT-IR) spectra analysis to study their morphological properties and porosity measurement, and functional group analysis, respectively. The abrupt morphological changes on the membrane surface and micro porosity formation at 800oC sintering temperature suggest that the synthesized clay based ceramic membrane could be used for various solid-liquid separations. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->